Disclosure of Sexual Orientation Among Women Who Have Sex With Women During Gynecological Care: A Qualitative Study In Brazil. Issue 7 (5th June 2018) - Rufino, Andréa Cronemberger; Madeiro, Alberto; Trinidad, Adriana Silva; Rodrigues dos Santos, Raiza; Freitas, Isadora
Abstract: Background: Evidence shows that women who have sex with women (WSW) face disparities in access to health care when compared to heterosexual women in several countries. Aim: To investigate the experiences WSW have after disclosure of sexual orientation during gynecological care in Brazil. Methods: We performed a qualitative study using content analysis. We recorded and transcribed interviews with 34 WSW from the 5 regions in Brazil. Data were analyzed using descriptive content analysis. Outcomes: The main categories of analysis were decision-making process to disclose and attitude of gynecologists after disclosure. Results: WSW disclosed their sexual orientation in an un-favorable environment. Gynecologists rarely asked about patients' sexual orientation and used a script for hetero-normative anamnesis. The reactions of gynecologists were discriminatory, resulting in abbreviated consultations and un-comfortable gynecological exams. They missed a window of opportunity for prevention, diagnosis, and treatment of various diseases. The experiences Brazilian WSW had during gynecological care demonstrated the dominant hetero-normativity in the health care scenario. The attitudes of the gynecologists precarized the existence of WSW in health service. Clinical Implications: This study suggests that gynecologists missed an opportunity to use WSW's sexual orientation disclosure to offer specific care to them. Strengths & Limitations: This is the first qualitative study about WSW's experiences during gynecological care in Brazil. Future studies should be developed from a wider sampling, especially among lower-class WSW. Conclusion: The results point out the need for a change in medical training and guidelines to assist WSW in the country.